Vegetational response to holocene climatic change: Pollen and palaeolimnological data from the Middle Atlas, Morocco (HOLOCENE, 1995)
Pollen data from a radiocarbon-dated lake-sediment core from the Middle Atlas of Morocco show that forests of evergreen and winter-deciduous oaks (Quercus rotundifolia, Q. canariensis), present from the start of the Holocene, were invaded at 6200 BP by Cedrus atlantica in low numbers. Two thousand years later, after a short period characterized by higher deciduous oak frequency, Cedrus increased to its present abundance. These changes may have been in response to increasing effective moisture as summer temperatures decreased with declining northern-hemisphere seasonality, under the influence of precessional forcing. Palaeolimnological data from the same core show that the lake level fell sharply in five 200-400 yr-long and intervals, but the pollen data show little or no evidence of a vegetational response. This suggests that summer (growing-season) rainfall remained adequate during the dry intervals, whereas depletion of the groundwater aquifer was the result of reduced winter precipitation. Anthropogenic exploitation since c. 1300 BP has had a greater effect on the forest ecosystem than any of the Holocene and intervals.